2020
DOI: 10.1007/s11481-020-09945-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress Enhances Proinflammatory Platelet Activity: the Impact of Acute and Chronic Mental Stress

Abstract: The role of platelets in hemostasis and thrombosis has long been recognized, recently their contribution to immunological and inflammatory processes is emerging. Platelets could be the missing link between cardiovascular disease, chronic stress and depressive symptoms. Both physical and mental stressors cause platelet activation reflected by changes in platelet bioactivity and aggregation. Here we evaluate the proinflammatory platelet response to acute and chronic mental stress. In a prospective study design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 50 publications
1
15
0
3
Order By: Relevance
“…First, the physiological stress response strongly influences hemodynamic parameters such as cardiac output, blood pressure, and heart rate ( 138 ). Second, activation of the different stress axes can also affect hemostatic parameters such as platelet activation ( 67 , 78 ). In the following sections, this review seeks to summarize experimental evidence for the third area: the inflammatory contribution of psychosocial stress to CVD risk ( Fig.…”
Section: Risk Factors Of Atherosclerosismentioning
confidence: 99%
“…First, the physiological stress response strongly influences hemodynamic parameters such as cardiac output, blood pressure, and heart rate ( 138 ). Second, activation of the different stress axes can also affect hemostatic parameters such as platelet activation ( 67 , 78 ). In the following sections, this review seeks to summarize experimental evidence for the third area: the inflammatory contribution of psychosocial stress to CVD risk ( Fig.…”
Section: Risk Factors Of Atherosclerosismentioning
confidence: 99%
“…An increased oxidative stress and hyperaggregability were observed in platelets of MMD cases compared to controls [141], as well as a higher content of serotonin, interleukin 1β, PF4 and CD40 ligand (CD40L) [142]. In line with this evidence, a recent longitudinal study on young males reported mental stress to be associated with increased and prolonged proinflammatory platelet bioactivity: while exposure to chronic stress led to an increased number of CD63 + platelets, acute stress was associated with alterations of CD62P + , CD63 + , PAC-1 + platelets and of platelet-leukocyte aggregates [143].…”
Section: Epidemiological Studiesmentioning
confidence: 66%
“…Thrombosis is the most common underlying pathology of stroke and CHD. A number of studies found that stressful states stimulated thrombosis that was coupled with increased count and activation of platelets, as well as impaired fibrinolytic system [31][32][33]. In the heart tissues of stressed mice, the gene sets (C3, C4b, etc.)…”
Section: Discussionmentioning
confidence: 99%